2018
DOI: 10.30526/2017.ihsciconf.1773
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Integrinα2 (ITGA2), Progesterone, Prolactin, Estradiol, Zinc and Vitamin C in Serum of Female Iraqi Patients with Breast Cancer

Abstract: Back ground: Cancer is the second leading cause of death throughout the world. Breast cancer, is one of the leading mortality reasons in women from Western Countries, in Iraq, breast cancer is the second reason of death After cardiovascular Diseases. Material and method: The study was carried out of period from October/2016-january /2017 and  included (90) serum samples for Iraqi women suffered from breast cancer . Samples were divided into two groups ,the first group included (66) patients (female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Breast carcinogenesis is a multistage transformation emerging from a combination of hereditary and environmental factors that lead to the advanced accumulation of epigenetic and genetic alterations in the cells of breast tissue [ 1 , 2 ]. The annual incidence rate of breast cancer ranges from 1% to 2% in developed countries; in less developed countries, the increase in the incidence can be up to 5% from that of developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Breast carcinogenesis is a multistage transformation emerging from a combination of hereditary and environmental factors that lead to the advanced accumulation of epigenetic and genetic alterations in the cells of breast tissue [ 1 , 2 ]. The annual incidence rate of breast cancer ranges from 1% to 2% in developed countries; in less developed countries, the increase in the incidence can be up to 5% from that of developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…In America, there will be 42,260 mammary malignancy decreases in 2019, according to estimates (4). Currently, after cardiovascular diseases, breast malignancy is the second largest cause of death for females in Iraq (5).…”
Section: Introductionmentioning
confidence: 99%
“…In America, there will be 42,260 breast cancer deaths in 2019, according to estimates (4). After cardiovascular diseases, breast neoplasm is the other largest cause of mortality for females in Iraq (5). Whereas the Iraqi Cancer Council reported that the proportion of females with breast cancer is 34.06% higher than that of…”
Section: Introductionmentioning
confidence: 99%